2015
DOI: 10.1039/c5ta07381b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning thermoelectric performance by nanostructure evolution of a conducting polymer

Abstract: The thermoelectric performance of PEDOT can be conveniently and effectively tuned by nanostructure evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(44 citation statements)
references
References 43 publications
(7 reference statements)
1
43
0
Order By: Relevance
“…Nanostructured PEDOT can exhibit high TE properties . Chen et al synthesized various PEDOT nanostructures by chemical polymerization in inverse microemulsions . They found that nanostructured PEDOTs can have higher charge carrier mobility than bulk PEDOT owing to more ordered polymer chains.…”
Section: P‐type Te Polymersmentioning
confidence: 99%
“…Nanostructured PEDOT can exhibit high TE properties . Chen et al synthesized various PEDOT nanostructures by chemical polymerization in inverse microemulsions . They found that nanostructured PEDOTs can have higher charge carrier mobility than bulk PEDOT owing to more ordered polymer chains.…”
Section: P‐type Te Polymersmentioning
confidence: 99%
“…In the past few years, the synthesis and investigation of nanostructured PEDOT for different applications are gaining increasing research interest [32][33][34][35][36][37][38][39]. In 2011, Taggart et al first investigated the thermoelectric properties of PEDOT nanowires, which were synthesized by oxidative electropolymerization of 3,4-ethylenedioxythiophene (EDOT) monomer in aqueous LiClO 4 solution via a hard template through a lithographically patterned nanowire electrodeposition (LPNE) approach with non-dependent control over the thickness and width of the nanowire (Figure 1) [34].…”
Section: Pedotmentioning
confidence: 99%
“…Therefore, the thermoelectric properties of PEDOT nanorods can be modified easily and efficiently [40]. In 2015, Hu et al reported the thermoelectric performance of nanostructured PEDOT with various morphologies (Figure 3a-e) by chemical oxidation polymerization in reverse microemulsions with sodium bis(2-ethylhexyl) sulfosuccinate (AOT) as the surfactant [35]. Tuning the quantity of oxidizing agent added and the rate of polymerization gave rise to PEDOT with different nanostructures, which were proved to have great effects on the thermoelectric properties (Figure 3f-h).…”
Section: Pedotmentioning
confidence: 99%
“…Compared with inorganic TE materials, conducting polymers based TE materials are low cost, good flexibility, and rich resources materials. Recently, conducting polymers and their composites TE materials have exhibited great potentials applied into TE filed and attracted more and more attention …”
Section: Introductionmentioning
confidence: 99%